American tegumentary leishmaniasis mimicking myiasis and granulomatous vasculitis: A case report - ARRIETA, VICTORIA JUDITH (2024)
Rationale: American tegumentary leishmaniasis comprises cutaneous and mucocutaneous manifestations caused by parasitic infections by various Leishmania species. Widespread across the Americas, it spans from the southern United States to northern Argentina. This report details the clinical intervention for a patient with American Tegumentary Leishmaniasis in Mendoza, Argentina, a non-endemic region.Patient Concerns: A 43-year-old male was admitted to a third-level hospital in Mendoza, Argentina Republic with a history of progressive nasal discharge, septal perforation, facial pain, and pruritus. Despite treatment for presumed nasal myiasis and vasculitis with granulomatosis, symptoms persisted.Diagnosis: American tegumentary leishmaniasis Interventions: Intravenous liposomal amphotericin B.Outcomes: Follow-up at 30 days showed no recurrence of symptoms with a remarkable clinical improvement of the nasal lesion.Lessons: This case sheds light on the necessity of accurate identification for timely intervention and the need to recognize the diverse manifestations of American Tegumentary Leishmaniasis to avoid misdiagnosis.